An Evaluation of Water Absorption Process Parameters for Composites by Deploying A Novel DEMATEL Method-PROMETHEE Method - Maduekwe, Victor Chidiebere; Oke, Sunday Ayoola (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2021)
Parametric ranking and selection in water absorption process of composite development are obligatory as they guide on resource distribution during the planning phase of composite development. However, the present literature model seems inaccurate as the PROMETHEE method fails to offer the likelihood of structuring the water absorption problem making it challenging to achieve a concise problem viewpoint and assess the results without difficulty. In this paper, the DEMATEL method is introduced to assign weights, revealing a cause and effect mechanism to overcome the aforementioned problem. The coupling point of the DEMATEL method-PROMETHEE method is at the weight determination of the DEMATEL method and the net outranking results are the final output of the model. Based on literature data, the DEMATEL method produced weights of 0.182, 0.114, 0.290, 0.242 and 0.244 for the parameters of final weight, initial weight, length, thickness and time, respectively. The PROMETHEE procedure yields the outranking results of -0.2166, -0.2742 and -0.0079 for the length, thickness and time, revealing time as the best parameter. The proposed method is user-friendly, complete in outranking, successful in real-world applications and capable to establish the cause and effect series constituent of the complicated water absorption system. The usefulness of this research is to help composite developers to achieve effective distribution of resource and decision regarding priority of parameters, leading to lean and effective manufacturing outcomes.